Редизайн тренінг-платформи для продавців - Гавриш, О. В. (ХНУРЕ, 2023)
Training salespeople can be very time-consuming. Platforms for sales training have begun to surface, helping to speed up business and increase education. Along with that, artificial intelligence is used to streamline coaches' tasks and qualitatively monitor the effectiveness of salespeople's work and training, which makes training platforms particularly valuable. This work is focused on conducting usability testing of one of the platforms and redesigning this platform based on the result of the conducted research. The final result of the work is a prototype with innovative design solutions for the new product
Keywords: тренування; тренінг-платформа